Changes in Renal Function Following Administration of Oral Sodium Phosphate or Polyethylene Glycol for Colon Cleansing before Colonoscopy. (2007) - Abaskharoun, Ramy; Depew, William; Vanner, Stephen
Abstract : Changes in renal function were compared in patients receiving oral sodium phosphate (NaP) for colon cleansing and those receiving large-volume polyethylene glycol (PEG) solution to determine whether oral NaP resulted in frequent renal damage that had gone clinically undetected. From 1995 to 2004, a cohort of consecutive patients who had serum creatinine (Cr) drawn immediately before colonoscopy and again after subsequent procedures three months to nine years later (almost 80% of patients between the first and fifth year) were identified. Chronic renal failure (CRF) was defined as an abnormal Cr at repeat measurement or an abnormal Cr clearance as estimated by the Cockroft-Gault equation at the time of repeat Cr measurement. Medications and medical comorbid conditions were recorded. Seven hundred sixty-seven patients (51% female and 49% male; 81% oral NaP and 19% PEG) with normal baseline Cr levels were identified through the endoscopy unit database at the Hotel Dieu Hospital, Queen's University (Kingston, Ontario). Of these, 55 (7%) developed CRF. Forty-two (6.8%) patients receiving oral NaP developed renal failure compared with 13 patients (8.7%) receiving PEG (Fisher's exact test; P=0.382), but the magnitude of CRF was small in each group (Cr level lower than 160 μmol/L). Using logistic regression analysis with the choice of preparation, medications and medical comorbid conditions as independent variables, only age and blood pressure were predictive of the development of renal failure (P=0.014 and P=0.001, respectively). Baseline Cr clearance was similiar in both the NaP and PEG groups and the absolute difference after colonoscopy did not differ. The present study concluded that the ingestion of oral NaP for colon cleansing before colonoscopy did not result in frequent renal damage that went clinically undetected.